Episteme, etc. : essays in honour of Jonathan Barnes - Barnes, Jonathan, 1942-; Morison, Benjamin; Ierodiakonou, Katerina (Oxford : Oxford University Press, 2011)
Sixteen authors, including some of the most distinguished scholars of our time, present essays which together reflect the impressive scope of Jonathan Barnes's contributions to philosophy, and in particular to the study of ancient philosophy. Six are on knowledge, five on logic and metaphysics and five are on ethics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Aristotle; Philosophy, Ancient; Knowledge, Theory of; Ethics, Ancient; Logic, Ancient; Metaphysics